A SIMPLE RP-HPLC METHOD DEVELOPMENT AND VERIFICATION FOR THE QUANTITATIVE ESTIMATION OF SODIUM BUTYRATE IN TABLETS - REDDY, BEMBADI MUKUND; REDDY, BHEEMI REDDY ASHOK; ASHOK KUMAR, AKUTHOTA; KODIPYAKA, RAVINDER; VOOTURI, RAJESH (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: To develop a simple, accurate, precise, and linear reverse-phase high-performance liquid chromatographic (RP-HPLC) method and verify the quantitative estimation (assay) of sodium butyrate in tablets. Methods: The optimized RP-HPLC method uses a reverse phase stationary phase which is YMC Triart C18 column, having specifications of 250×4.6 mm; 5 μm, a mobile phase composition of pH 8.0 sodium dihydrogen phosphate buffer and acetonitrile in the proportion of 92:8 v/v, flow rate of 0.5 ml/min, injection volume of 10 μL, and detection wavelength of 210 nm using a UV/PDA detector. Results: The developed method gave sodium butyrate eluting at about 6 min. Sodium butyrate exhibited linearity in the range of 119.56–1195.6 μg/ ml. The precision was exemplified by a relative standard deviation of 0.30%. The percentage of individual recovery was found to be in the range of 97.0 and 103.0 during accuracy studies. Conclusion: A simple, specific, accurate, precise, and linear RP-HPLC method was developed and verified for the quantitative estimation (assay) of sodium butyrate in tablets and hence this method can be explored for the analysis of sodium butyrate in tablets in various pharmaceutical industries.